LANDASAN FILOSOFIS INTEGRASI ILMU ISLAM DAN SAINS: TELAAH ATAS KRISIS PENDIDIKAN ISLAM KONTEMPORER - Johanna Nuryanto Putra; Dimas Halvin; Anharudin; Amril M; Liana Novita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the philosophical crisis in contemporary Islamic education, which encompasses ontological, epistemological, and axiological dimensions. This crisis is characterized by a shift in the orientation of Islamic education from the formation of the “insan kamil” (the perfect human being) toward a pragmatic and formalistic approach, a dichotomy between religious and general knowledge, and a weakening of the integration between revelation and reason within the educational system. This situation has caused Islamic education to lose its spiritual, moral, and humanistic orientation amidst the tide of modernity and the advancement of science. This study aims to analyze the ontological, epistemological, and axiological problems in Islamic education and to formulate a paradigm for the integration of Islamic knowledge and science as a conceptual solution. The study employs a qualitative approach using library research (literature review). Data were collected from various sources, including books, scientific journal articles, and relevant prior research, and analyzed using descriptive-analytical and philosophical-critical approaches. The results of the study indicate that the reconstruction of Islamic education requires an integrative paradigm that combines revelation and reason, eliminates the dichotomy of knowledge, and restores the orientation of education toward the values of tawhid, ethics, humanity, and the public good. The integration of Islamic knowledge and science is a strategic step toward building a holistic, dialogical, humanistic, and relevant Islamic education capable of addressing contemporary challenges